Measuring Students' Perceptions of Constructivist Learning Environments Linked to Understanding of Rasch Modeling-Based Chemical Concepts - Sofia Buoki; Lukman Abdul Rauf Laliyo; Haris Munandar; Akram La Kilo; Masrid Pikoli; Julhim S. Tangio; Najmah Najmah (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
This study aims to evaluate the suitability of data obtained from the Constructivist Learning Environment Survey instrument and a multiple-choice chemistry understanding test, as well as to examine the relationship between students' perceptions of the constructivist learning environment and their understanding of chemistry concepts. A non-experimental, quantitative descriptive approach was employed, involving 519 12th-grade science students from five high schools in Gorontalo Province during the even semester of the 2024/2025 academic year. Data analysis was conducted using the Rasch model via Winsteps 3.73 software to assess instrument quality, and SPSS software to test data normality and analyze correlations. The results indicated that both instruments were valid and reliable, with person reliability of 0.81, item reliability of 0.99, and Cronbach’s Alpha exceeding 0.80—classified as excellent. A Pearson correlation analysis revealed that the calculated r value exceeded the critical value (rcount= 0.135 > rtable= 0.087), indicating a statistically significant, albeit weak, positive relationship between students’ perceptions and their chemistry understanding. The hypothesis testing results showed that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted, confirming the existence of a relationship between students’ perceptions of constructivist learning environments and their understanding of chemistry concepts.